Glycemic Index of gluten-free bread and their main ingredients : a systematic review and meta-analysis - Romão, Bernardo (2021)
This study aimed to perform a systematic review and meta-analysis of the glycemic index (GI) of gluten-free bread (GFB) and its main ingredients. The systematic review followed PRISMA guidelines, using seven electronic databases (PubMed, EMBASE, Scopus, Science Direct, Web of Science, gray literature research with Google Scholar, and patents with Google Patent tool), from inception to November 2020. Eighteen studies met the inclusion criteria evaluating 132 GFB samples. Five articles tested GI in vivo, eleven in vitro; and two studies tested both methods. The analysis showed that 60.7% (95% CI: 40.2–78.1%) of the samples presented high glycemic indexes, evidencing a high glycemic profile for GFB. Only 18.2% (95% CI: 11.7–27.2%) of the bread samples presented in the studies were classified as a low GI. Meta-analysis presented moderate/low heterogenicity between studies (I2 = 61% and <1% for both high and low GIs) and reinforced the proportion of high GIs. Lower GIs were found in formulations based on Colocasia esculenta flour or enriched with fiber, yogurt and curd cheese, sourdough, psyllium, hydrocolloids, enzymes, fructans, and resistant starch, highlighting the efficacy of these ingredients to lower GFBs’ GI. GFB tends to present high GI, impacting the development of chronic diseases when consumed.